2005
DOI: 10.3748/wjg.v11.i34.5367
|View full text |Cite
|
Sign up to set email alerts
|

Esophagectomy for locally advanced esophageal cancer, followed by chemoradiotherapy and adjuvant chemotherapy

Abstract: For locally advanced esophageal cancer, the combination of esophagectomy, post-operative CCRT with weekly cisplatin and systemic adjuvant chemotherapy is well tolerated and effective. A large-scale, prospective randomized trial of this regimen is in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Curative surgery of the esophagus is usually performed for lesions of the gastroesophageal junction and the middle or lower third of the thoracic esophagus. Radiationtherapy and chemotherapy may be added [11][12][13][14][15]. Surgery for the squamous cell carcinoma of the cervical esophagus is very extensive and cause major functional impairments and high morbidity and mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Curative surgery of the esophagus is usually performed for lesions of the gastroesophageal junction and the middle or lower third of the thoracic esophagus. Radiationtherapy and chemotherapy may be added [11][12][13][14][15]. Surgery for the squamous cell carcinoma of the cervical esophagus is very extensive and cause major functional impairments and high morbidity and mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that hematogenous metastasis was the main cause of failure in the S + R group. As 2 recent studies have suggested that postoperative chemotherapy can decrease lymphoma metastasis and increase progression-free survival [20,21], and several retrospective analyses have demonstrated that postoperative concurrent chemoradiotherapy enhanced OS compared with surgery alone or postoperative chemotherapy [22,23,24], we intend to optimize postoperative IMRT and chemotherapy together in future studies to decrease hematogenous metastasis. Our next study will focus on how to decrease hematogenous metastasis.…”
Section: Commentmentioning
confidence: 99%
“…Patients with unresectable or medically inoperable disease are usually treated with concurrent radiotherapy and chemotherapy for preoperative or definitive treatment. [2][3][4] Although various chemotherapy regimens are available, esophageal cancer carries a very poor prognosis, with a mean survival time of less than 8.1 months. 5 Currently, neoadjuvant treatment (such as capecitabine and cisplatin with concurrent radiotherapy (RT) followed by esophagectomy) is considered the effective treatment for esophageal cancer, 6,7 leading to complete pathologic response at the time of surgical resection and improved local tumor control and eradication of micrometastases.…”
Section: Introductionmentioning
confidence: 99%